Influence of Direct Laser Written 3D Topographies on Proliferation and Differentiation of Osteoblast‐Like Cells: Towards Improved Implant Surfaces. (25th August 2014) - Hohmann, Judith K.; von Freymann, Georg
<x xml:space="preserve">Abstract</x> The influence of truly three‐dimensional microstructures on osteoblast‐like cells is reported. Well defined templates are fabricated by direct laser writing and biocompatibly coated with titanium dioxide, resembling implant surfaces. The influence of structural parameters on proliferation, morphology, adhesion, and differentiation is studied. A significantly higher proliferation (170%) is observed on particular topographies compared to unstructured surfaces. Additionally, an influence of structural parameters on the morphology of osteoblast‐like cells is obtained, whereas all cells possess the osteoblastic marker alkaline phosphatase within all structures.